Nursing stress and patient care: real‐time investigation of the effect of nursing tasks and demands on psychological stress, physiological stress, and job performance: study protocol. (6th February 2013) - Farquharson, Barbara; Bell, Cheryl; Johnston, Derek; Jones, Martyn; Schofield, Pat; Allan, Julia; Ricketts, Ian; Morrison, Kenny; Johnston, Marie
Abstract Aim To examine the effects of nursing tasks (including their physiological and psychological demands, and the moderating effects of reward and control) on distress and job performance in real time. Background Nurses working in hospital settings report high levels of occupational stress. Stress in nurses has been linked to reduced physical and psychological health, reduced job satisfaction, increased sickness absence, increased staff turnover, and poorer job performance. In this study, we will investigate theoretical models of stress and use multiple methods, including real‐time data collection, to assess the relationship between stress and different nursing tasks in general medical and surgical ward nurses. Design A real‐time, repeated measures design. Methods During 2011/2012, 100 nurses from a large general teaching hospital in Scotland will: (a) complete self‐reports of mood; (b) have their heart rate and activity monitored over two shifts to obtain physiological indices of stress and energy expenditure; (c) provide perceptions of the determinants of stress in complex ward environments; and (d) describe their main activities. All measures will be taken repeatedly in real time over two working shifts. Discussion Data obtained in this study will be analysed to examine the relationships between nursing tasks, self‐reported and physiological measures of stress and to assess the effect of occupational stress on multiple work outcomes. The results will inform theoretical understanding of nurse stress and its determinants and suggest possible targets for intervention to reduce stress and associated harmful consequences.